Kecemasan Preoperasi pada Pasien yang Akan Menjalani Operasi Appendiktomi: Kecemasan Preoperasi pada Pasien yang Akan Menjalani Operasi Appendiktomi - Ramba, Erni; Tania, Elly; Citraningtyas, Theresia (Universitas Kristen Krida Wacana, 2024)
Anxiety is an individual's reaction to unexpected situations that everyone often experiences in life, providing warnings and directing someone to try to protect themselves. The process of surgery or surgery can cause anxiety reactions. This literature review aims to determine the description of anxiety in preoperative appendicitis patients and the factors that can influence the patient's preoperative anxiety level. Research articles in the form of clinical trials and randomized control trials were reviewed using the Google Scholar search engine, using specific keywords such as anxiety AND